Recent Progress on Pyrazole Scaffold‐Based Antimycobacterial Agents. Issue 5 (27th March 2015) - Keri, Rangappa S.; Chand, Karam; Ramakrishnappa, Thippeswamy; Nagaraja, Bhari Mallanna
<x xml:space="preserve">Abstract</x> New and reemerging infectious diseases will continue to pose serious global health threats well into the 21st century and according to the World Health Organization report, these are still the leading cause of death among humans worldwide. Among infectious diseases, tuberculosis claims approximately 2 million deaths per year worldwide. Also, agents that reduce the duration and complexity of the current therapy would have a major impact on the overall cure rate. Due to the development of resistance to conventional antibiotics there is a need for new therapeutic strategies to combat Mycobacterium tuberculosis. Subsequently, there is an urgent need for the development of new drug candidates with newer targets and alternative mechanism of action. In this perspective, pyrazole, one of the most important classes of heterocycles, has been the topic of research for thousands of researchers all over the world because of its wide spectrum of biological activities. To pave the way for future research, there is a need to collect the latest information in this promising area. In the present review, we have collated published reports on the pyrazole core to provide an insight so that its full therapeutic potential can be utilized for the treatment of tuberculosis. In this article, the possible structure–activity relationship of pyrazole analogs for designing better antituberculosis (anti‐TB) agents has been discussed and is also helpful for new thoughts in the quest for rational designs of more active and less toxic pyrazole‐based anti‐TB drugs.